the crisis of the Victory Movement through the testimonies of party activists and some historical writings “a comparative study” - abbou, nadjet (The Algerian Historical Journal, 2026)
Historical reports dealt with the crisis of the movement for the victory of democratic freedoms and recorded testimonies and stories from certain party activists. However, anyone who studies this subject note that there is a big difference in the views of party activists on the crisis, each having their own point of view, and this according to their ideological and political convictions. In this article, we will attempt to conduct a historical comparative study of the testimonies of party activists, comparing the testimony of one of the parties to the conflict and the testimony of the neutral party of party members.